A study on human-centered design approach in software development process (analysis phase) from management level perspectives / Nor Adilah Abd Razak - Abd Razak, Nor Adilah (2012)
An information system brings a huge advantage to human as users as well as to the organizations today. The discipline of system engineering over the past five decades has used a software development life cycle methodology as a foundation to develop an information system. A good requirement in the system will produce a good system which benefits to organizations, users and marketplace. Analysis phase is the most effective phase in software development process as to develop a good requirement for a system at the early stage of development project. Human Centered Design is an approach that involves users from both organizational and end-users in the development processes. The aims of this study are to identify the concept of Analysis phase in SDLC process, to investigate the HCD principles applies during Analysis phase and to investigate the HCD elements applies in Analysis phase. Hence, this study proposed the guidelines based on HCD approach for Analysis phase in SDLC process. This study focuses on management perspectives which involving top management and middle management in the Malaysia's software house organizations. Therefore, by using HCD approach as a foundation in proposed guidelines which integrate with Analysis phase in SDLC processes, this guidelines will be benefits to all stakeholders and users in developing quality products that can satisfy user's needs and brings good reputations to the organization as well as profitability in the business marketplace.